2020
DOI: 10.3390/cancers12102967
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin Is Induced in Non-Alcoholic Fatty Liver Disease and Hepatitis B-Related Hepatocellular Carcinoma

Abstract: Chemerin is protective in experimental models of hepatocellular carcinoma (HCC). Noteworthy, chemerin mRNA and protein were reduced in HCC tissues of Asian patients with mostly hepatitis B disease etiology. The current study nevertheless showed that chemerin protein was induced in tumor tissues of European HCC patients with non-alcoholic fatty liver disease (NAFLD) and patients with unclear disease etiology. A similar regulation was observed in hepatitis B virus (HBV), but not in hepatitis C virus (HCV), relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
15
1
Order By: Relevance
“…Many studies in rodent models indicate that chemokines play a crucial role in NAFLD. 28,29 The levels of CCL20 were increased in the animal models of liver injury, especially with the acute-on-chronic condition. 30 Results from a network meta-analysis showed that the concentrations of chemokines, including CCL20, in the NASH group were higher than those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in rodent models indicate that chemokines play a crucial role in NAFLD. 28,29 The levels of CCL20 were increased in the animal models of liver injury, especially with the acute-on-chronic condition. 30 Results from a network meta-analysis showed that the concentrations of chemokines, including CCL20, in the NASH group were higher than those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the participants were summarized in Table 3 . Tissues of patients with viral infections were used in a previous study to measure chemerin and CMKLR1 in the liver tissues [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although chemerin is protective in experimental models of HCC, chemerin was reported to be induced in tumor tissues of patients with HBV-related HCC [57].…”
Section: Chemerinmentioning
confidence: 99%